The theses for MD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
Z.V. Gesheva — NSAID-gastropathies at juvenile arthrites (risk factors, prevention, treatment) D.A. Kakhramanova — Combination of gastroesophageal reflux disease to 2nd type diabetes mellitus: features of course and potential of early diagnostics of complications